Impact of digitalization of information processes on controllers’ profession: A systematic literature review - Szukits, Ágnes; Sztrida, Lilla; Szabó, Inez Anna (Vezetéstudomány / Budapest Management Review, 2024)
Based on a systematic review of the international literature, this paper investigates how the digitalization of information processes shapes the role of controllers in supporting decision-making. Drivers of this transformation include the increased amount of data and the diffusion of advanced data analytics techniques. At the same time, the available ‘new types’ of decision-relevant data are no longer primarily financial and accounting in nature, so other professional groups have entered the field of decision-supporting data analytics. These changes rightly raise the question of what added value controllers create in managerial decision support. Based on our synthesis, we argue that controllers as become marginal in data analytics, their importance increases in the areas of interpreting results, sense-making and trust building. Advances in data analytics lead to jurisdictional problems, and the cooperation not only with other professional groups but with the technology itself raises new questions.